PENGELOLAAN BANK SAMPAH DI KOTA ADMINISTRASI JAKARTA BARAT TAHUN 2018 (Studi Kasus: Kota Administrasi Jakarta Barat, DKI Jakarta) - Hana Nova Yanti; Hening Darpito; Deni Kurniawan (FT-USNI, 2019)
One way of managing inorganic waste is to make a waste bank. In principle, a waste bank is a place to save waste that has been sorted according to the type of waste. The purpose of this research is to find out information and an in-depth description of the management of waste bank in West Jakarta Administration City which includes operational technical aspects, financing aspects and aspects of community participation. The method used is qualitative method with descriptive research type. Data analysis using qualitative analysis. The results obtained are waste management by making a waste bank is an effective way to reduce waste generation and make the environment clean especially for densely populated areas.